ANALISIS PERBANDINGAN ATAS MODEL REVALUASI ASET TETAP SESUAI PSAK NO. 16 (REVISI 2007) DAN DAMPAK PERPAJAKANNYA MENURUT UNDANG-UNDANG PAJAK - Chandra pribadi; Nurmiati nurmiati (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2016)
The purpose of this study was to determine how the impact of revaluation of fixed assets to corporate taxation. This research was conducted in PDAM Tirta Jaya Mandiri Sukabumi. The method of analysis in this research is descriptive qualitative non-statistical (non Descriptive Statistics). The results of the research that revaluation memiliiki impact on the final income tax where the impact of the activities of revaluation of fixed assets is the excess of the revaluation of fixed assets subject to final tax of 10%. Companies can save on taxes by 7% (assuming the petition filed since October 31, 2015 until December 31, 2015 and charged at 3%). Companies can save on taxes by 6% (assuming the petition filed since January 1, 2016 until the date of June 30, 2016 and charged at 4%) or save 4% (assuming the petition filed since July 1, 2016 until December 31, 2016 and charged at 6%). Discount rate provided by the government in 2015 was never used by the company, whereas the discount rate is the opportunity for the company to undertake the revaluation (revaluation) of fixed assets. Companies should consider doing a reassessment (revaluation) on fixed assets in return taking into account the positive impact for the company arising from such activities.Keywords: PSAK No.16, Revaluation of Fixed Assets, Fixed Asset Revaluation Impact.